2021
DOI: 10.4187/respcare.09257
|View full text |Cite
|
Sign up to set email alerts
|

2020 Year in Review: Mechanical Ventilation During the First Year of the COVID-19 Pandemic

Abstract: Corona virus disease 2019 represents the greatest medical crisis encountered in the young history of critical care and respiratory care. During the early months of the pandemic, when little was known about the virus, the acute hypoxemic respiratory failure it caused did not appear to fit conveniently or consistently into our classification of acute respiratory distress syndrome (ARDS). This not only reignited a half-century's long simmering debate over taxonomy, but also fueled similar debates over how PEEP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 198 publications
(338 reference statements)
0
5
0
Order By: Relevance
“…However, these findings are novel because COVID-19 illness may not be entirely comparable to previous causes for ARDS. Firstly, there is controversy regarding the phenotypes underlying traditional ARDS and respiratory failure due to COVID-19 illness [19]. Secondly, the clinical presentation for respiratory failure in COVID-19 has been demonstrated to be more variable and non-uniform than what is traditionally seen in ARDS [19,64].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these findings are novel because COVID-19 illness may not be entirely comparable to previous causes for ARDS. Firstly, there is controversy regarding the phenotypes underlying traditional ARDS and respiratory failure due to COVID-19 illness [19]. Secondly, the clinical presentation for respiratory failure in COVID-19 has been demonstrated to be more variable and non-uniform than what is traditionally seen in ARDS [19,64].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, there is controversy regarding the phenotypes underlying traditional ARDS and respiratory failure due to COVID-19 illness [19]. Secondly, the clinical presentation for respiratory failure in COVID-19 has been demonstrated to be more variable and non-uniform than what is traditionally seen in ARDS [19,64]. With these facts in mind, comparing outcomes following MV treatment for COVID-19 illness and non-COVID-19 ARDS is difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to recent findings, the need for a specific ventilator approach could be guided by the identification of COVID-19 phenotypes (1 or L and 2 or H) [ 29 ], taking into account the risk of aerosol generator procedures, as well as the development of patient self-inflicted lung injury (P-SILI) [ 30 ]. In another perspective, preemptive intubation was proposed to avoid progressive acute respiratory failure [ 31 ]. Recent data confirmed that in patients receiving NIV, late intubation was associated with worse clinical presentation and more severe disease than early, suggesting that the delay in intubation might have an impact on patient’s outcome [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients with COVID-19-associated acute respiratory failure has or eventually develops ARDS. 61 Elevated respiratory drive in ARDS is multifactorial, and it is impossible to gauge the specific contributions of any one sensory input. Common characteristics associated with ARDS include rapid shallow breathing and vigorous inspiratory effort.…”
Section: Respiratory Drive In Ardsmentioning
confidence: 99%